Mechanical performance of pineapple leaf fibre reinforced polylactic acid biocomposites - Ramli, Siti Nur Rabiatutadawiah (UTeM, 2018)
To-date, there is a large body of knowledge in the literature on the development of biocomposites. Nonetheless, some of the main limitation is the brittleness of the biocomposites when using PLA matrix which lead to relatively poor mechanical performance of the biocomposites. Thus, the main objectives of this research project are (i) to evaluate the effect of alkaline pre-treatment and fibre length on PALF reinforced biocomposites; (ii) to determine the effect of varying PLA matrix on the mechanical properties of the biocomposites and (iii) to study the effect of strain rate on the impact response of PALF reinforced PLA biocomposites (quasi-static vs. dynamic loading). The pineapple leaf fibre was pre-treated using sodium hydroxide (NaOH) prior to fabrication. The biocomposite with fibre loading of 30 wt.%. were fabricated either using two-step compression moulding (long fibre biocomposites) or melt-mixing and compression moulding (short fibre biocomposites) with fibre length of approximately 30 mm and 150 mm respectively. Following these, the biocomposites were characterized in terms of their flexural properties as a function of fibre length, surface modification and use of different grades of the PLA matrix, in accordance with ASTM D 790. Sodium hydroxide was found to augment mechanical performance by promoting enhanced adhesion at the fibre/matrix interface. Alkaline-treated biocomposites exhibit much greater flexural strength and modulus in comparison to those of the untreated samples, an indication of an improved interfacial bonding between the fibre and the matrix, as evident in the SEM micrographs, with rough surface on the alkaline-treated PALF. Moreover, the flexural properties of the biocomposites exhibit superior performance when fabricated using long PALF (150 mm) rather than the short PALF (30 mm), suggesting an efficient load transfer capability. In addition, the biocomposite samples based on PLA 6100D grade exhibit superior flexural and tensile properties, relative to those of the 3251D based biocomposites, due to its ductile nature. In addition, thermal analysis of the PLA matrices showed that different degree of crystallinity is observed for both types of matrices. Lastly, in terms of strain rate effect, results following quasi-static and dynamic loading on the long PALF reinforced biocomposites show that higher magnitude of the maximum force and greater amount of damage are present in the biocomposites when subjected to the dynamic loading. In addition, the PLA 6100D based biocomposites exhibit significantly much better performance in flexural, tensile and impact tests compared to 3251D based biocomposites. These findings suggest that fibre length, matrix material, surface modification and strain rate have an effect on the mechanical performance of the pineapple leaf fibre reinforced biocomposites.